Tanggungjawab Pelaku Usaha Bagi Konsumen Terhadap Keamanan Pangan Dalam Prespektif Hukum Perlindungan Konsumen - Juldin Latama; Nirwan Junus; Mellisa Towadi; Nurul Fazri Elfikri (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Food safety in Indonesia is still far from safe, we often see food poisoning incidents that occur a lot nowadays. In general, this often results in consumers being in a weak and disadvantaged position, so there is a need for regulations that can bridge the interests of business actors and the interests of consumers without harming either party. Forms of responsibility of a business actor towards consumers in the legal order in Indonesia Civil liability based on legal events can be divided into two, namely: liability based on fault, namely liability that can arise due to breaches of contract or unlawful acts, whether caused by careless actions or intentional actions. Responsibility based on risk is the responsibility that must be borne by a business actor for his business activities which cause losses to consumers.